FeO–alumina catalyst for reforming waste polyethylene terephthalate (PET) pyrolyzed products: synthesis, characterization, and performance evaluation - Audu, Ephraim Akuaden; Ade-Ajayi, Adebola Femi; Osigbesan, Aisha Ayoola; Gano, Zaharaddeen Sani; Barminas, Jeffrey Tsware (Comptes Rendus. Chimie)
The growing rate of plastic pollution in Nigeria and across the globe, coupled with the need to harness such waste for useful purposes, is a pressing global concern. In this study, a new type of catalyst was synthesized by incorporating mesoporous FeO onto aluminium oxide trihydrate (alumina) and applied in reforming polyethylene terephthalate (PET) pyrolyzed gas into valuable fuels. The pyrolysis process was carried out at 500 °C while vapor reforming was carried out using 0.5 g of catalyst loading in a fixed bed reactor at 450 °C for 90 min. Scanning electron microscopy analysis of catalysts revealed particle sizes of 1.42–7.63, 1.37–10.75, and 2.66–6.34 μm for alumina, 3% FeO/Al, and 5% FeO/Al, respectively. The percentage compositions of Fe in the synthesized catalyst from the X-ray fluorescence results were found to be 4.7% and 3.62% for 5% FeO/Al and 3% FeO/Al, respectively. XRD analysis revealed that the synthesized catalysts were non-crystalline. Catalyst performance evaluation from the gaseous product revealed a decrease in oxygen from 23.3% in the blank run to 5.33% in 5% FeO/Al. The H2 content was found to be highest in 5% FeO/Al with a value of 17.14% while the CH4 content was found highest in 3% FeO/Al (16.22%). Fourier transform infrared analysis of the liquid products inferred peaks corresponding to aromatic and saturated hydrocarbons, which was confirmed by gas chromatography mass spectrometry analysis. Findings from this research demonstrated that the synthesized catalyst was able to reform waste PET pyrolyzed gas into valuable products, addressing environmental challenges and providing alternative energy sources.